Adherence to the Healthy Eating Index-2015 across generations and associations with birth outcomes and weight status at age 5 years: results from the Lifeways Cross Generation Cohort Study in Ireland. (November 2018) - Navarro, Pilar; Mehegan, John; Murrin, Celine M; Kelleher, Cecily C; Phillips, Catherine M; ,
Abstract: Background: Maternal dietary quality during pregnancy is associated with birth outcomes. Limited data about similar paternal influences on offspring outcomes exist and these associations have not been examined in three-generation families. We investigated the intra-uterine hypothesis by comparing maternal, paternal, and grandparental lineage influences of dietary quality on offspring birth outcomes and weight status at age 5 years in a three-generation familial cohort in Ireland, the Lifeways Cross Generation Cohort Study. Methods: The cohort comprised 1094 live infants born to 1082 mothers recruited at first antenatal booking appointment; 333 fathers and 707 grandparents also completed the baseline questionnaire. Dietary scores, determined with the Healthy Eating Index (HEI)-2015, were generated for expectant mothers, fathers, and up to four grandparents from prenatal dietary information collected using a validated food frequency questionnaire. Birth outcomes were abstracted from hospital records, and body-mass index was determined when the child was 5 years old. Associations were assessed by logistic regression. Findings: Mean maternal and paternal HEI scores were 52·0 (SD 8·6) and 47·7 (9·4), respectively. After adjustment for confounders, greater adherence to maternal HEI was associated with lower risk of low birthweight (odds ratio 0·72, 95% CI 0·50–0·99; p=0·040). Similarly, maternal grandmothers with higher HEI scores were less likely to have grandchildren with low birthweight (0·87, 0·61–0·96; p=0·042) and more likely to have macrosomia (1·10, 1·01–1·22; p=0·033). Higher HEI scores of paternal and paternal grandmothers were associated with lower risk of childhood obesity (0·89, 0·30–0·94; p=0·034) and overweight grandchildren at 5 years (0·83, 0·22–0·99; p=0·043). Mediation analysis showed significant direct effects of HEI scores of both maternal and paternal grandmothers on grandchildren's birthweight (β=0·0006, p=0·035) and obesity (−0·0459, p=0·034). Interpretation: Higher HEI-2015 scores were associated with lower risk of low birthweight in the maternal and maternal grandmother lines, whereas higher paternal and paternal grandmother dietary quality predicted lower risk of childhood overweight and obesity. These data suggest that differential intergenerational transmission of risk exists between maternal and paternal lines, whereby maternal line dietary quality appears to influence fetal growth and paternal line dietary quality appears to influence postnatal growth. Funding: Irish Health Research Board (reference HRC/2007/13).